PENGARUH KINERJA KEUANGAN DAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024) - Sani, Sani; Widyaningsih, Atria Tiffany; Suseno, Joko (STIE 'INDONESIA' Pontianak, 2025)
The purpose of this study is to determine and analyze the effect of financial performance and earnings management on the value of companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024. The data used in this study are secondary data. The analysis of research data uses multiple linear regression. The research variables are financial performance, earnings management and company value. Using the cluster sampling method to take samples. The number of samples in this study was 30 service companies. The F test and t test and determination analysis were used to determine the magnitude of the influence of financial performance and earnings management. The results of this study indicate that the variables of financial performance and earnings management have an effect on company value.